Implementasi Pembelajaran Bahasa Arab dengan Modul Pembelajaran Menulis 3 Jam di LKP Jogja Kaligrafi - Annisa Farizky Nurul Janah (Mahira: Journal of Arabic Studies & Teaching, 2024)
This study aims to determine the implementation of the module “Training for Easy and Fluent Arabic Writing 3-Hour System” at LKP Jogja Calligraphy. The research was conducted in a descriptive qualitative manner with data collection techniques through observation, interviews, and documentation. The research subjects included the director, management, teaching staff, and students. The results showed that the implementation of the module was carried out through four main stages: introduction of hijaiyah letters and their classification, formation of letters that change shape, practice writing single and connected letters, and habituation of independent practice istiqomah. Supporting factors for implementation include LKP's strategic position as a calligraphy training center, community enthusiasm, and institutional legality. The obstacles faced include limited human resources and costs, participants' lack of understanding of instructions, and technical obstacles in the learning process such as short training duration, difficulty in drawing calligraphy, lack of learning innovation, and challenges in using special stationery.